Search for biological mechanisms of toxic action of shoe glues: cell viability in vitro, albumin damage and free radical generation - U.B. Lototska-Dudyk; B.P. Kuzminov; L.B. Lototska; O.Yu. Klyuchivska; R.S. Stoika (Medičnì Perspektivi, 2025)
The combined use of cellular, extracellular research methods for studying the toxic effect of shoe glues is an additional tool for screening and assessing the potential risks of their use. The aim of the work was to investigate the mechanisms of the toxic effect of shoe glues at the cellular, molecular and biochemical levels. Rubber, polychloroprene and polyurethane shoe glues were used. Three experimental approaches were applied: measurement of survival of mammalian cells, a spectroscopic study of conformational changes of albumin, and a free radical measurement. Cytotoxicity testing was performed on murine fibroblasts Balb/c-3T3 line, human embryonic kidney cells HEK-293 and human keratinocytes of the HaCaT line treated for 24 and 72 hours with glues samples. A survival of treated cells was monitored using MTT-test. Changes in the spectral characteristics of albumin were monitored during exposure for 24 hours and 21 days with "fresh" and "dried" samples of glues. Content of free radicals was evaluated in the reaction with DPPH reagent. The cytotoxicity was increased with increasing exposure time, and depended on both the type of glue and the type of treated cells. The polyurethane glue demonstrated the most pronounced cytotoxic effect. Balb/c-3T3 fibroblasts were the most sensitive to the action of all types of glues, a reliable maximum increase in cell death was manifested in 72 hours exposure (28.9-19.1% of living cells).While cells of HEK-293 and НаСаТ lines were more resistant. At 24 hours contact, their viability was 99.12-79.22% and 99.0-56.9%, respectively. Increased exposure up to 72 hours reliably caused a decrease in the survival of these cell lines – 96.24-68.1% and 82.2-51.7%. The loss of the solvent didn’t affect the cytotoxic effect of the studied glues. Conformation changes in albumin were manifested during its long-term contact with both "fresh" and "dried" glues. Manifestations of the toxic effect of glues on biomolecules were increased in the sequence: rubber > polyurethane > polychloroprene. Shoe glues demonstrated an ability to generate free radicals in the sequence: rubber > polychloroprene > polyurethane. These manifestations were increased in a time period of 4 hours – 24 hours. That may create risks when they are used. The results can be used to determine the targets and mechanisms of the toxic effect of shoe glues and to obtain new knowledge in the field of research of industrial toxicants.